Analisis Konsep Fluida Pada Canting Cecek Siji - Sulistiani Sulistiani; Fita Widiyatun; Indica Yona Okyranida; Neng Nenden Mulyaningsih (UNIVERSITAS INDRAPRASTA PGRI, 2022)
The canting is one of the simple tools used in the batik process, which consists of a handle, a container/place for the liquid wax, and a pipe/cucuk as a way out of the liquid wax as well as for inscribing the liquid wax onto the batik cloth. The purpose of this study is to examine the fluid concept contained in the canting. The method used is literature study. The results obtained are that there is a principle of continuity in Canting cecek siji.